THE IMPACT OF PIRACY IN ELIZABETH RUDNICK S PIRATES OF THE CARIBBEAN: THE CURSE OF THE BLACK PEARL - Malolo, Surya Randa; Mamentu, Agustine C.; Sabudu, Delli (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The objective of the present study is to find out the impact of piracy in Elizabeth Rudnick s novel Pirates of the Caribbean: The curse of the Black Pearl< em> The methodology which the writers applied in this research is the qualitative method with the mimetic approach to analyze the data The source of the data in this research is Elizabeth Rudnick s novel Pirates of the Caribbean: The Curse of the Black Pearl< em> which was published by Disney Press in 2006 The result of this research shows that piracy affects the human and the environment Piracy also affects the underwater ecosystem and creates pollution It is suggested that more investigation be done to examine the larger effects of piracy on both the natural environment and human settings To lessen the harmful effects of piracy on the underwater ecosystem and minimize contamination initiatives should also be made to increase awareness and encourage responsible behavior < p>